"The Dresden Story": Racism, Human Rights, and the Jewish Labour Committee of Canada - Lambertson, Ross (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2001)
Abstract This article uses a case study to explore how organized labour, particularly the Jewish Labour Committee, contributed to the development of human rights values and anti-discrimination law in the immediate post-war period. The study focuses on the town of Dresden, Ontario, which at one time was infamous for its treatment of blacks. When a number of organizations (including labour groups) lobbied the Ontario government to create Canada's first Fair Accommodation Practices Act, they pointed to Dresden as an example of why this legislation was necessary. After the legislation was passed, they used litigation to ensure that discrimination in Dresden would come to an end. The paper demonstrates that, although the trade union movement in Canada was not free from racism, it nevertheless played an important and under-appreciated role in fighting for egalitarian human rights.